Infecção por Leishmania sp. em cães de Florianópolis, Santa Catarina, Brasil - Pacheco, Acácio Duarte [UNESP]; Laurenti, Marcia Dalastra; de Lima, Valéria Marçal Félix [UNESP]; Tomokame, Thaise Yumie; Marcondes, Mary [UNESP] (Universidade de São Paulo. Agência de Bibliotecas e Coleções Digitais, 2013)
The aim of the present study was to investigate the occurrence of Leishmania sp. infection in dogs (N = 491) living in the municipality of Florianópolis, Santa Catarina (SC), Brazil, which was considered a disease-free region for visceral leishmaniasis until 2011, when autochthonous cases of canine disease were notified. Seroprevalence in this population was assessed by ELISA (0.4%; 2/491) and IFAT (4.09%; 24/491). Only one dog exhibited seroreactivity in both serological methods, comprising a total of 25 (5.3%) seroreagent animals. Leishmania sp. DNA, obtained from a sample of whole blood of this animal, was amplified by both conventional and Real-Time PCR. Sequencing of the amplified DNA and, thereby, determination of the Leishmania species involved, was not possible. Our results suggest the necessity of a thorough epidemiological investigation in Florianópolis.
Leishmania sp. Infection in dogs from Florianópolis, Santa Catarina, SC, Brazil
Keywords: Diagnosis; ELISA; IFAT; PCR; Visceral leishmaniasis